Fit, Female or Fifty–Is Cardiac Rehabilitation “Fit” for Purpose for All? A Systematic Review and Meta-Analysis With Meta-Regression - Smith, Martin; Orchard, Jessica; La Gerche, Andre; Gallagher, Robyn; Fitzpatrick, Jane (Frontiers in Cardiovascular Medicine, 2022)
Aims: Cardiac rehabilitation (CR) is an evidence-based intervention promoting risk factor modification following coronary artery disease events but the relative benefits for patient subgroups is not clear. This review synthesises the available evidence on the effectiveness of modern CR programs and determines outcomes for age, sex and prior level of fitness. Methods: MEDLINE, CINAHL, and EMBASE were examined for RCT and cohort studies involving exercise prescription or phase II or III CR following Myocardial Infarction (MI), Percutaneous Coronary Intervention (PCI) and cardiac surgery from January 2010 to February 2021. Outcomes assessed included peakVO2max, 6-minute walk test and Metabolic Equivalent of Task. Meta-regression was used to determine CR impact for change in fitness and age and sex influences. Results: The mean age of study participants was 59.5 years and 82.7% were male. Females, younger people and those of average or above cardiorespiratory fitness were substantially under-represented in data and attendance, with 13% of study groups with a mean age <55 years. At entry, 73% were below average for fitness versus age-matched normative values. Fitness improved across all groups following CR with no evidence of sex or age independently affecting outcomes. Conclusions: Modest improvements in fitness in all groups were shown, but the benefits of CR can be far greater. A modern, innovative approach to CR will likely lead to more substantial benefits. This may require a ‘Precision Medicine’ model which tailors exercise prescription to different populations to ensure all CR participants’ needs are met. This will ensure that CR is more flexible and accessible for all.